Corrosion behaviour and properties of Mg–3.4Y–3.6Sm–2.6Zn–0.8Zr Alloy in 3.5 wt-% NaCl solution. (3rd October 2022) - Wang, Wenli; Ke, Jing; Guo, Lintong
ABSTRACT: The applications of magnesium alloys are limited because of their poor corrosion properties. In this study, the corrosion behaviours of Mg–3.4Y–3.6Sm–2.6Zn–0.8Zr alloy in 3.5 wt-% NaCl solution were investigated, the results suggested that the precipitations of rare-earth phase, (Mg, Zn)3 (Y, Sm) and Mg12 (Y, Sm) Zn, are beneficial to enhance the anti-corrosion of magnesium alloys. The network second phase, (Mg, Zn)3 (Y, Sm), may act as an anode. It can form a galvanic couple with the adjacent α-Mg matrix and effectively protect the α-Mg matrix. The existence of the Mg12 (Y, Sm) Zn phase makes the distribution of the (Mg, Zn)3 (Y, Sm) phase more uniform, which may produce a more uniform electrochemical structure and reduce the galvanic corrosion. Under the dual action of the two second phases, the corrosion performance of Mg–3.4Y–3.6Sm–2.6Zn–0.8Zr alloy was better than that of the standard AZ31B alloy. The corrosion mechanism of the alloy is galvanic corrosion due to the second phase with low potential.